Design, Synthesis and Catalytic Evaluation of Mono- and Polynuclear Organometallic Materials as Hydroformylation Catalysts - Omosun, Nikechukwu Nike (Department of Chemistry, 2022)
The hydroformylation reaction is an important homogeneous rhodium-catalyzed industrial process for the production of linear and branched aldehydes from readily available alkenes. The aldehydes produced serve as major building blocks for valuable chemical and pharmaceutical products. The fast-depleting and expensive, highly-active rhodium metal has triggered an interest in the design and synthesis of new, more efficient, selective and recyclable rhodium-based catalysts. The strategies of introducing hydrophilic substituents, multiple active sites and bulky dendritic ligands are currently explored to enhance catalyst performance and recyclability. This study investigated the synthesis, characterisation and catalytic potential of new water-soluble alpha-diimine Rh(I) complexes, alpha-diimine Rh(I) metallodendrimers and a water-soluble binuclear Rh(I) complex. New water-soluble disulfonated 1,4-diazabutadiene (DAD) ligands bearing either an ethyl or acenaphthene backbone were prepared. The alpha-diimine N,N-chelating ligands were synthesised via the Schiff base condensation reactions of 4-aminophenol with 1,2-ethanedione or acenapthenequinone, followed by sulfopropylation reactions with 1,3 propanesultone. Complexation of the water-soluble ligands with the rhodium precursor [Rh(COD)(MeCN)2]BF4 (where COD = 1,5-cyclooctadiene) yielded new water-soluble alphadiimine Rh(I) complexes. In addition, non-sulfonated 1,4-diazabutadiene (DAD) Rh(I) analogues were synthesised by complexation of the alpha-diimine Schiff base ligands with [Rh(COD)(MeCN)2]BF4. The complexes were fully characterised using 1H, 13C{1H} NMR spectroscopy, IR spectroscopy and electrospray ionisation mass spectrometry. The complexes were successfully evaluated as catalyst precursors in the hydroformylation of 1-octene. The reaction conditions were optimised at 75 ℃, 40 bar syngas pressure for 4 h with 2.87 x 10-3 mmol catalyst loading. The sulfonated 1,4-diazabutadiene Rh(I) complexes displayed excellent conversion of 1-octene (> 98%) and good chemoselectivity towards aldehydes (> 86%) while the non-sulfonated 1,4-diazabutadiene Rh(I) complexes displayed lower catalyst activity. Recyclability of the disulfonated 1,4-diazabutadiene Rh(I) complexes were successfully conducted over 4 cycles, with a loss in catalytic activity after the third cycle. Inductively coupled plasma optical spectrometry experiments confirmed negligible leaching of the catalyst precursors into the organic layer. Additionally, catalytic experiments in the presence of mercury show unsuppressed catalyst activity, thus suggesting that the hydroformylation reaction is mediated by a molecularly-dispersed homogeneous species. A series of Fréchet-type dendrons with methyl ester groups at the periphery were subsequently prepared. The α-diimine (DAD) Schiff base ligands were synthesised and coupled to the Fréchet-type dendrons via a Williamson ether reaction to yield a new series of alpha-diimine poly(aryl ether) (PAE) dendrimers with methyl ester groups at the periphery. Complexation of the alpha-diimine poly(aryl ether) (PAE) dendrimers with the metal-precursor [Rh(COD)(MeCN)2]BF4 afforded the three generations of core-functionalised α-diimine Rh(I) metallodendrimers. The dendritic ligands and their corresponding Rh(I) metallodendrimers were fully characterised using standard spectroscopic and analytical techniques. The core-functionalised alpha-diimine rhodium(I) metallodendrimers were applied as catalyst precursors in the hydroformylation of 1-octene and styrene. For the hydroformylation of 1- octene, the metallodendrimers gave good conversions (> 81%) and good aldehyde chemoselectivity (> 83%) under optimum reaction conditions of 75 ℃, 40 bar syngas pressure over 4 h. With respect to regioselectivity, an increase in dendritic generation of the rhodium complexes increased the regioselectivity towards linear aldehydes. For the hydroformylation of aromatic-substituted olefin (styrene), the regioselectivity of the three generations of metallodendrimers were comparable. Therefore, the increased steric crowding around the metal centre had no effect in improving regioselectivity towards linear aldehyde for aromaticsubstituted olefinic substrates. Mercury poisoning experiments performed using the three generations of Rh(I) metallodendrimers displayed suppressed activity (< 52%). This is indicative of a catalytic system that follows a combination of homogeneous and heterogeneous pathway. Lastly, the synthesis and characterization of water-soluble tetrasulfonated tetraimine and disulfonated diimine ligands are described. The ligands were synthesized via the Schiff base condensation reactions of 4-hydroxybenzaldehyde with 3,3-diaminobenzidine or o-phenylenediamine, followed by nucleophilic reactions with 1,3 propanesultone. Complexation reactions of the water-soluble ligands with [Rh(COD)(MeCN)2]BF4 afforded water-soluble mononuclear and binuclear Rh(I) complexes. Both complexes displayed excellent water-solubility at room temperature. The compounds were characterised using an array of spectroscopic (1H, 13C{1H} NMR, FT-IR spectroscopy) and analytical (mass spectrometry) techniques. The sulfonated mononuclear and binuclear Rh(I) complexes were evaluated as catalyst precursors in the aqueous biphasic hydroformylation of 1-octene under hydroformylation conditions of 75 ℃, 40 bar syngas pressure for 4 h. Both catalyst precursors gave good catalytic conversion (> 96%) and aldehyde chemoselectivity (> 87%). Notably, the presence of an extra metal centre in the binuclear complex led to an increase in catalyst activity. Recyclability experiments were conducted over 4 cycles, with a significant drop in conversion after each cycle. The drop in catalyst performance may be attributed to catalyst degradation often associated with the reuse of the same catalyst containing phase.